Харовые водоросли (Charales) Житомирского Полесья (Украина) - Борисова, Е.В.; Орлов, А.А. (Альгология, 2009)
Приведены результаты изучения видового состава харовых водорослей (Charales) Жито-мирского Полесья. Обнаружено девять видов, относящихся к родам Chara L. (5) и Nitella C. Agardh (4). Показано, что на исследованной территории наиболее часто встречаются редкие виды Ch. delicatula C. Agardh, N. flexilis (L.) C. Agardh, N. mucronata (A. Braun) Miq. in H.C. Hall, занесенные в Красный список Charales Украины, и значительно реже Ch. contraria A. Braun ex Kütz., Ch. fragilis Desv. in Loisel., Ch. vulgaris L., широко распространенные в Украине. Впервые для Житомирского Полесья приводятся Ch. aspera Dethard. ex Willd. и N. gracilis (Sm.) C. Agardh. Подтверждена для данной территории (после 1972 г.) находка N. capillaris (Krock.) J. Groves et Bull.-Webst. Проведено сравнение видового состава Charales Житомирского Полесья с таковым Волынского и Киевского. Отмечены особенности их распространения в водоемах всего Правобережного Украинского Полесья. The results of a study on species composition of the Zytomir Polissia charophytes (Charales) are presented. Nine taxa belonging to the genera Chara L. (5) and Nitella C. Agardh (4) were found. It was shown that Ch. delicatula C. Agardh, N. flexilis (L.) C. Agardh, and N. mucronata (A. Braun) Miq. in H.C. Hall, rare species in the Red Check List of Charales of the Ukraine, occur most frequently within the investigated territory whereas Ch. contraria A. Braun ex Kütz., Ch. fragilis Desv. in Loisel., and Ch. vulgaris L., widespread species, are less frequent in these investigated territories. Ch. aspera Dethard. ex Willd. and N. gracilis (Sm.) C. Agardh are first cited for Zytomir Polissia. A record of N. capillaris (Krock.) J. Groves et Bull.-Webst. is confirmed for this territory (after 1972). The species composition of Charales of Zytomir Polissia was compared to those of Volyn and Kiev Polissia. Species distribution of Charales in water bodies throughout the Right-Bank Ukrainian Polissia has been revealed.